Can Peasants Make a Revolution? Colonialism, Labour, and Power Relations in Pierre Bourdieu's Algerian Inquiries*. (5th December 2016) - Rapini, Andrea
Abstract: This article analyses the Algerian inquiries of Pierre Bourdieu. It begins by retracing the most pervasive, medium- and long-term interventions of French colonial power in Algerian society: the introduction of capitalism and the internment of civilians in the centres de regroupement . Next, it outlines the social subjects studied by the young agrégé of philosophy and his representation of labour. Subsequent sections deal with shifts in the public stance of Bourdieu regarding the revolutionary propensity of these people. On this tricky testing ground, Bourdieu engaged with and critically confronted the ideas of Germaine Tillion and Frantz Fanon. His position is reviewed from a historical-philological approach in order to set the texts in their temporal and spatial contexts, establish parallels and/or divergences, and verify the effects such comparisons produced. The conclusions emphasize the richness and originality of Bourdieu's inquiries given the era in which they were made and highlight, in light of the recent global reorientation of labour history, some of the vital viewpoints expressed on the origins of capitalism in the colony. Abstract : TRANSLATED ABSTRACTS FRENCH – GERMAN – SPANISH Andrea Rapini. Les paysans peuvent-ils faire la révolution? Le colonialisme, les travailleurs et les relations de pouvoir dans les enquêtes algériennes de Pierre Bourdieu . Cet article analyse les études algériennes de Pierre Bourdieu. Il commence par retracer les interventions les plus répandues à moyen et à long terme de la puissance française coloniale en Algérie: l'introduction du capitalisme et l'internement de civils dans les centres de regroupement . L'auteur analyse ensuite les sujets sociaux que le jeune agrégé de philosophie étudie et la représentation qu'il fait des travailleurs. Les parties suivantes portent sur les changements dans la position publique de Bourdieu concernant la propension des travailleurs à faire la révolution. Sur ce terrain d'essai délicat, Bourdieu examine les idées de Germaine Tillion et de Frantz Fanon, en les abordant dans une perspective critique. Sa position est étudiée selon une approche historico-philosophique pour replacer les textes dans leur cadre temporel et spatial, établir des parallèles et/ou des divergences et vérifier les effets que ces comparaisons produisent. Les conclusions soulignent la richesse et l'originalité des recherches de Bourdieu pour l'époque à laquelle elles furent faites et mettent en valeur, à la lumière de la récente réorientation globale d'histoire du travail, certains points de vue essentiels qui y sont exprimés sur les origines du capitalisme dans la colonie. Traduction: Christine Plard Abstract : Andrea Rapini. Können Bauern eine Revolution machen? Kolonialismus, Arbeiterklasse und Machtverhältnisse in Pierre Bourdieus Untersuchungen zu Algerien . Dieser Beitrag analysiert Pierre Bourdieus Untersuchungen zu Algerien. Einleitend werden die tiefgreifendsten mittel- und kurzfristigen Interventionen der französischen Kolonialmacht in die algerische Gesellschaft rekonstruiert: die Einführung des Kapitalismus und die Inhaftierung von Zivilisten in den centres de regroupement . Anschließend werden die sozialen Subjekte skizziert, die der junge agrégé in der Philosophie untersuchte, ebenso seine Darstellung der Arbeiterklasse. Die darauf folgenden Abschnitte befassen sich mit den Veränderungen in den öffentlichen Äußerungen Bourdieus hinsichtlich der revolutionären Neigungen dieser Menschen. Auf diesem verfänglichen Untersuchungsterrain setzte sich Bourdieu kritisch mit den Ideen Germaine Tillions und Frantz Fanons auseinander. Seine Position wird von einem historisch-philologischen Standpunkt aus betrachtet, damit die Texte in ihre zeitlichen und räumlichen Kontexte gestellt, Parallelen bzw. Unterschiede bestimmt und die von solchen Vergleichen gezeitigten Effekte überprüft werden können. Abschließend wird die Reichhaltigkeit und Originalität betont, die Bourdieus Untersuchungen im Vergleich zu anderen Texten der Zeit auszeichnet, und es werden, mit Blick auf die jüngere globale Neuausrichtung der Geschichte der Arbeit, einige der wesentlichen Perspektiven Bourdieus auf die Ursprünge des Kapitalismus in der Kolonie hervorgehoben. Übersetzung: Max Henninger Abstract : Andrea Rapini. ¿Pueden los campesinos hacer una revolución? Colonialismo, trabajo y relaciones de poder en los planteamientos de Pierre Bourdieu sobre Argelia . En este texto se analizan los planteamientos de Pierre Bourdieu sobre Argelia. Comienza por poner recordar las intervenciones más persiasivas a medio y largo plazo del poder colonial francés en la sociedad argelina: la introducción del capitalismo y el internamiento de civiles en los centres de regroupement . A continuación se subrayan los sujetos sociales estudiados por el joven agrégé de Filosofía y su representación de trabajo. Las secciones siguientes tratan de los cambios en la esfera pública de Bourdieu tomando en consideración la propensión revolucionaria de las personas que la componían. En este delicado ámbito de análisis Bourdieu se acabó enfrentando con las ideas defendidas por Germaine Tillion y Frantz Fanon, planteando una confrontación crítica. Su posición se analiza desde una perspectiva histórico-filológica para situar los escritos en sus contextos temporales y espaciales, estableciendo paralelismos y/o divergencias, y comprobando los efectos que resultan de tales comparaciones. Las conclusiones permiten enfatizar la riqueza y originalidad de los planteamientos de Bourdieu para una época en la que estos fueron hechos y pone de relieve, a la luz de la reciente reorientación global de historia del trabajo, alguno de los puntos de vista vitales expresados sobre los orígenes del capitalismo en la colonia. Traducción: Vicent Sanz Rozalén